Hydroponic System with Integrator Modified on PI Controller for Nutrient and Water Regulation - Ihsan Auditia Akhinov; Nuralam Nuralam; Sri Lestari Kusumastuti; Bernadeta Siti Rahayu Purwanti; Adjie Nur Fadhilah (TEPIAN, 2024)
— This study developed a hydroponic control system to regulate nutrient concentration (PPM) and water volume using a Proportional-Integral (PI) controller. The PI controller was chosen for its simplicity and effectiveness in systems that do not require fast response times. A trial-and-error method was used to tune the Kp and Ki values, which were implemented in an ATMega328 microcontroller. The system consists of one AC pump and two DC pumps: DC Pump-1 controls the PPM by supplying liquid fertilizer, while DC Pump-2 regulates the water volume. The results showed that modifying the PI controller with an integrator limitation improved performance. For PPM control, a limit of 13000 with Kp = 2 and Ki = 0.01 resulted in a 0.5% error, 56.8-second rise time, and a 4.8% overshot. For water level control, a limit of 12000 with Kp = 100 and Ki = 0.16 yielded a 3.25% error, 2% overshot, and a 65.4-second rise time. The test results demonstrated that the use of AB Mix can be reduced by up to 26% compared to a conventional PID, with an initial PPM value of around 350.